EPP Satisfaction on Discourse Grounds: The Case of Locative Inversion. (29th June 2019) - Ojea, Ana
Abstract: This article approaches locative inversion as a construction resulting from valuation of the core intentional feature [DI] (for discourse intention ) by a locative constituent to obtain an event‐reporting thetic statement that expresses a state of affairs located in some spatiotemporal coordinates. I argue that in languages where [DI] is an EPP feature, as is the case with Spanish, the locative is internally merged in Spec, TP, competing with the subject for this position with respect to prominence conditions. Two types of locative‐inversion constructions therefore obtain: (i) core locative inversion, where the locative phrase is structurally prominent, and (ii) deictic locative inversion, where the locative phrase is nonprominent but must be merged in Spec, TP for reasons of interface economy. The article explores in detail the differences between the two and the predicted differences between Spanish and other languages, such as English, where the EPP is not informational but formal in nature. It also offers empirical support for Spec, TP as the landing site of the locative in Spanish (and, it is predicted, in other discourse‐prominent languages), showing that locative inversion is not a root phenomenon in this case and can therefore be found in many contexts where standard topicalization would be ruled out.